Fatigue-related changes in technique emerge at different timescales during repetitive training - Aragonés, D.; Eekhoff, A.; Horst, F.; Schöllhorn, W. I. (Journal of Sports Sciences, 2018)
Training consisting of numerous repetitions performed as closely as possible to ideal techniques is common in sports and every-day tasks. Little is known about fatigue-related technique changes that emerge at different timescales when repeating complex actions such as a karate front kick. Accordingly, 15 karatekas performed 600 kicks (1 pre-block and 9 blocks). The pre-block comprised 6 kicks (3 with each leg) at maximum intensity (K-100%). Each block comprised 60 kicks (10 with each leg) at 80% of their self-perceived maximum intensity (K-80%) plus 6 K-100%. In between blocks, the participants rested for 90 seconds. Right leg kinematics (peak joint angles, peak joint angular velocities, peak joint linear resultant velocities, and time of occurrence of peaks) and kick duration corresponding to the K-80% were measured resulting in numerous variations with fatigue. At the timescale of tens of seconds, the changes involved variables that were related to velocity of execution (slowed down), while variables related to movement form were hardly affected. At the timescale of tens of minutes, the opposite results were observed. These findings challenge the long-standing rationale underlying repetitive training, suggesting instead that such involuntary variations in technique might play a crucial role in motor skill training